Textural and minerachemical significance of hornblendes from an andesite at Dir, Kohistan arc, N. Pakistan - Hamidullah, Syed; Shah, Mohammad Tahir (Journal of Himalayan Earth Sciences, 1993)
Petrography and minerachemical features of a hornblende andesite from Gira Khwar, northeast of Dir proper, are studied to envisage the crystallization mode of hornblende phenocrysts, in the rock. It is determined that the cores of the hornblende phenocrysts are primary igneous. On the other hand the bluish green rims of these phenocrysts and probably the goundmass hornblende are a product of subsolidus re-equilibration and or metamorphic recrytallization. The very tips of the hornblende Phenocrysts appear to have recrystallized during shearing and cataclasis at a latter stage.